Listy zastawne jako instrument finansowania lokalnego rynku nieruchomości - Sitek, Marcin (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
In the late 90-years the legislation which normalized activity of hypo banks in Poland and emission letters of pawn was passed. In compliance with this law hypo banks and the letters of pawn are applied to region related with immovable markets. In future besides communal bonds, a letter of pawn will perhaps occur important finance instrument of the local immovable markets. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 526-533